Emulation of System as Strategy for Teaching of Mechanical System - Alberto Pérez Rodríguez, Jesús; Gina Rodríguez Borges, Ciaddy; Vázquez Pérez, Antonio; Alejandro Bowen, Carlos (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this work is to demonstrate how emulated systems can support teaching-learning processes, as well as supporting tools for mechatronic systems design practices of low and medium complexity. In the engineering design process, it is necessary to make a prototype to verify compliance with the parameters and restrictions posed in the design conditions, but the construction of these prototypes can be expensive, especially as the device becomes more complex, in order to show the usefulness of emulated systems in the context of mechatronic systems projects, an experience was developed aimed at developing a filling and sealing system for plastic tubes, following the steps of the engineering design process, to build a virtual prototype and emulate it in order to test the control strategies of the equipment with commercial devices (LCD), the process was carried out with excellent performance and at low costs, evidencing its potential for teaching and stimulating skills and abilities in the design phase.